Strategi Self-Control Mahasiswa dalam Menghadapi Konsumerisme Digital - Hariani, Farida; Haris, Hasnawi; Awaru, A. Octamaya Tenri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explain the self-control strategies used by students in dealing with consumptive behaviour in the digital age. The phenomenon of digital consumerism is growing rapidly due to the ease of access to online shopping and the strong influence of social media promoting a fast-paced lifestyle. This study uses a qualitative method with a literature review approach that examines the results of previous studies, both from national and international journals, relevant to consumptive behaviour, the use of digital platforms, and students' self-control strategies. The analysis was conducted through a process of identification, selection, and thematic synthesis to obtain a comprehensive picture of the most widely used self-control mechanisms. The results of the study show that students apply several main strategies, such as setting financial priorities, limiting the duration of shopping app usage, applying self-awareness through personal reflection, and increasing financial literacy to reduce impulsive urges. These findings confirm that strengthening self-control plays an important role in building healthier and more adaptive consumption patterns for students amid the rise of digital consumerism.